Diastolic dysfunction in women with ischemia and no obstructive coronary artery disease: Mechanistic insight from magnetic resonance imaging. (15th May 2021) - Samuel, T. Jake; Wei, Janet; Sharif, Behzad; Tamarappoo, Balaji K.; Pattisapu, Varun; Maughan, Jenna; Cipher, Daisha J.; Suppogu, Nissi; Aldiwani, Haider; Thomson, Louise E.J.; Shufelt, Chrisandra; Berman, Daniel S.; et al.
Abstract: Background: Ischemia with no obstructive coronary artery disease (INOCA) is prevalent in women and is associated with increased risk of developing heart failure with preserved ejection fraction (HFpEF); however, the mechanism(s) contributing to this progression remains unclear. Given that diastolic dysfunction is common in women with INOCA, defining mechanisms related to diastolic dysfunction in INOCA could identify therapeutic targets to prevent HFpEF. Methods: Cardiac MRI was performed in 65 women with INOCA and 12 reference controls. Diastolic function was defined by left ventricular early diastolic circumferential strain rate (eCSRd). Contributors to diastolic dysfunction were chosen a priori as coronary vascular dysfunction (myocardial perfusion reserve index [MPRI]), diffuse myocardial fibrosis (extracellular volume [ECV]), and aortic stiffness (aortic pulse wave velocity [aPWV]). Results: Compared to controls, eCSRd was lower in INOCA (1.61 ± 0.33/s vs. 1.36 ± 0.31/s, P = 0.016); however, this difference was not exaggerated when the INOCA group was sub-divided by low and high MPRI ( P > 0.05) nor was ECV elevated in INOCA (29.0 ± 1.9% vs. 28.0 ± 3.2%, control vs. INOCA; P = 0.38). However, aPWV was higher in INOCA vs. controls (8.1 ± 3.2 m/s vs. 6.1 ± 1.5 m/s; P = 0.045), and was associated with eCSRd ( r = −0.50, P < 0.001). By multivariable linear regression analysis, aPWV was an independent predictor of decreased eCSRd (standardized β = −0.39, P = 0.003), as was having an elevated left ventricular mass index (standardized β = −0.25, P = 0.024) and lower ECV (standardized β = 0.30, P = 0.003). Conclusions: These data provide mechanistic insight into diastolic dysfunction in women with INOCA, identifying aortic stiffness and ventricular remodeling as putative therapeutic targets. Highlights: INOCA is prevalent in women and is associated with increased risk of developing HFpEF. The mechanism(s) contributing to heart failure progression in women with INOCA remains unclear. Here we show that elevated aotric stiffness is an independent predictor of impaired diastolic function in INOCA.